Marriage of unequals? investment quality heterogeneity, market heat, and the formation of status-asymmetric ties in the venture capital industry - ZHELYAZKOV, Pavel I. (Institutional Knowledge at Singapore Management University, 2021)
In this study, we investigate the emergence of status-asymmetric ties among venture capital firms. In particular, we highlight the venture's performance trajectory as a powerful antecedent of upward-status asymmetries (in which a lower-status actor brings a higher-status alter into a venture) as well as downward-status asymmetries (in which a higher-status actor brings in a lower-status alter). We hypothesize that lower-status firms tend to bring higher-status alters into ventures on a better performance trajectory, whereas higher-status firms tend to bring lower-status alters into poorly performing ventures. Furthermore, we argue that these effects will be moderated by market heat, which affects whether investors would focus on the upside or downside of deals. We test our hypotheses in a longitudinal analysis of venture capital syndication patterns in the United States between 1990 and 2017. We find support for most of our predictions and document that the ability of lower-status lead investors to bring higher-status followers into good ventures is particularly accentuated in hot markets, which can heighten market participants' concerns about missing good deals. We thus highlight the interplay between the internal and the external contexts in shaping the formation of status-asymmetric relationships.